Trace element concentrations and geochronologic data of zircon from ignimbrites from the Northern Yemen section of the Afro-Arabian large igneous provicne - Jennifer E Thines; Ingrid Anne Ukstins; Corey Wall; Mark D Schmitz (PANGAEA, 2021)
Silicic volcanic rocks (primarily ignimbrite, tuff, and volcanic breccia) were collected in the Sana extquotesinglea region, Yemen section of the Afro-Arabian large igneous province in 1999. Rock descriptions are available in Ukstins Peate et al. (2005; doi: 10.1007/s00445-005-0428-4). Zircon from four samples (three ignimbrites, one caldera collapse breccia) was separated and analyzed for trace element concentrations and uranium-lead isotope ratios at the Boise State University Isotope Geology Laboratory. Trace element concentrations and uranium-lead isotope ratios were obtained from laser ablation-inductively-coupled mass spectrometry (LA-ICP-MS) over three days in November 2019. Preliminary uranium-lead dates were calculated and are reported to two standard deviations. 32 zircon crystals were selected for chemical abrasion-thermal ionization mass spectrometry (CA-TIMS) analysis. Dissolved zircons were spiked with ET535 mixed uranium-lead tracer solution prior to uranium and lead separation using hydrochloric acid-based anion-exchange chromatography. Uranium-lead isotope ratios and dates obtained from TIMS analysis are reported to two standard deviations.